تأثير الساد واستخراجه على قياس سماكة ألياف العصب البصري بواسطة ال OCT. - جلول قحطان; سليمان يوسف; الدرويش صلاح الدين (Latakia University Journal -Medical Sciences Series, 2019)
Introduction:The purpose of this study is to determine the effect of cataract surgery by phacoemulsfcation on the measurement of retinal nerve fiber layer using spectral domain optical coherence tomography(OCT). Patients and methods :This research included 50 persons of ophthalmology clinic visitors at Tishreen University Hospital in Lattakia, their ages were from 40 to 80 years. The study included 32 males and 18 females, with no other ocular morbidity except cataract and planned for phacoemulsifcation . All patients underwent imaging with OCT one day before surgery and at 1 month after surgery. Results :The mean age of subjects was 62.1± 5.8years. The average RNFL increased from 99.28± 11.618 μm to104.71 ± 15.908 μm after phacoemulsiFcation, an increase of 5.43 % (P = 0.005). Pre- and postoperative overall quadrant RNFL thickness differences were statistically significant in all quadrants with the exception of the temporal quadrant (increase in superior quadrant3.02%,inferior quadrant 7.18%,nasal quadrant11.56%), increase in the temporal quadrant 0.02%.The change in RNFL thickness was maximum in posterior subcapsular cataract followed by cortical and nuclear subtypes. Conclusions:A signifcant increase in RNFL thickness was observed after cataract surgery using OCT. The maximum change in RNFL thickness was in the inferior quadrant where RNFL thinning is a signifcant predictor of glaucoma progression. The posterior subcapsular cataract interfered with RNFL measurement maximally due to its density and proximity to nodal point. After the cataract surgery, a new baseline needs to be established by, obtaining fresh OCT images for assessing the longitudinal follow-up of a glaucoma patient. المقدمة :الهدف من هذه الدراسة هو تحديد تأثير جراحة الساد بواسطة الأمواج فوق الصوتية على طبقة الألياف العصبية الشبكية (RNFL)بواسطة التصوير المقطعي المتماسك البصري( OCT). المواد و الطرائق :شملت العينة على 50 مريض من مراجعي العيادة العينية في مشفى تشرين الجامعي باللاذقية. بلغ عدد الذكور32 وعدد الإناث 18. وتتراوح الأعمار بين 40 إلى 80سنة. المرضى المشخص لديهم ساد بدون أي مشاكل عينية أخرى تم إدخالهم بالدراسة وأجراء فحص عيني شامل لهم وأجراء صورة OCT لطبقة الألياف العصبية الشبكية(RNFL) قبل يوم من العمل الجراحي وبعد شهر واحد من العمل الجراحي. النتائج :العمر الوسطي 5.8± 62.1سنة. زاد معدل سماكة RNFL من 11.61± 99.28 إلى 15.908± 104.71,بقيمة 5.43%(0.005 =P) بعد جراحة الساد بالأمواج فوق الصوتية. كان هناك فرق هام إحصائيا في سماكة أرباع RNFL قبل وبعد الجراحة باستثناء الربع الصدغي (الزيادة في الربع العلوي3.02%, السفلي7.18%, الأنسي 11.56%), الزيادة بالربع الصدغي0.002%.التغير الأعظمي كان في الساد تحت المحفظة الخلفية ثم الساد القشري ثم الساد النواتي. الاستنتاجات :يوجد زيادة هامة ملحوظة في سماكة RNFL بعد جراحة الساد بالأمواج فوق الصوتية مقاسة بواسطة OCT.التغير الأعظمي في سماكة RNFL كان في الربع السفلي, حيث يعتبر ترقق الربع السفلي مؤشر تنبؤي هام في تطور الزرق. الساد تحت المحفظة الخلفي هو المؤثر الأعظم نظرا" لشدته وقربه من النقطة العقدية. بعد جراحة الساد, إجراء صور OCT باكرة لطبقة الألياف العصبية الشبكية(RNFL) لتحديد خط قاعدي جديد للمرضى الذين يحتاجون متابعة من أجل الزرق.